Penerapan Alat Pelindung Diri Sebagai Upaya Keselamatan Dan Kesehatan Kerja Di Pabrik Tahu Dan Tempe - Etika Sari Sari; Junarsih Junarsih; Rizkya Fataya Guchi (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Occupational Health and Safety is all science and its application to prevent work accidents, occupational diseases, fires, explosions and environmental pollution. Work accident prevention efforts are needed to avoid losses that arise and to improve work safety performance in the workplace. One of the efforts that can be done to reduce work accidents is to use personal protective equipment. In PkM Activities, which are carried out by providing education regarding the importance of applying personal protective equipment to support occupational safety and health. The purpose of this PkM is to provide knowledge and insight. The results of the education that have been carried out can increase the knowledge and awareness of workers in order to avoid work accidents and occupational diseases.